The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1051/0004-6361/201424592
|View full text |Cite
|
Sign up to set email alerts
|

The Type IIb SN 2011dh: Two years of observations and modelling of the lightcurves

Abstract: We present optical and near-infrared (NIR) photometry and spectroscopy as well as modelling of the lightcurves of the Type IIb supernova (SN) 2011dh. Our extensive dataset, for which we present the observations obtained after day 100, spans two years, and complemented with Spitzer mid-infrared (MIR) data, we use it to build an optical-to-MIR bolometric lightcurve between days 3 and 732. To model the bolometric lightcurve before day 400 we use a grid of hydrodynamical SN models, which allows us to determine the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 48 publications
(81 reference statements)
6
95
0
Order By: Relevance
“…This mixup was also propagated to Fremling et al (2014). 15 We use the LC data of SN 2011dh from Ergon et al (2014Ergon et al ( , 2015.…”
Section: Extinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mixup was also propagated to Fremling et al (2014). 15 We use the LC data of SN 2011dh from Ergon et al (2014Ergon et al ( , 2015.…”
Section: Extinctionmentioning
confidence: 99%
“…Further, the progenitor of the wellobserved Type IIb SN 2011dh has been shown by Ergon et al (2014Ergon et al ( , 2015 to most likely be a composite of a nearly completely stripped compact He core with a mass of 3.3-4.0 M surrounded by a thin H-rich envelope extending out to 200-300 R . Binary evolution modeling can readily reproduce these properties at the time of explosion, while single-star models encounter difficulties in reproducing the relatively low ejecta mass in combination with the observed H shell (Claeys et al 2011;Benvenuto et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The broadband optical photometry from day 888 Andrews et al 2010), andSN 1993J (red;Tinyanont et al 2016). Data for SN 2011dh (yellow;Helou et al 2013;Ergon et al 2015) andSN 1998S (magenta;Gerardy et al 2002;Pozzo et al 2004) are also included for comparison.…”
Section: Warm Spitzermentioning
confidence: 99%
“…This methodology is applied to every epoch of each SN for which a pre-explosion reference image exists. We checked our photometry against IRAC photometry of SN 2011dh presented by Ergon et al (2015) between 18 and 1061 days post explosion. The results agree to within 5%.…”
Section: The Supernova Sample and Spitzer/irac Photometrymentioning
confidence: 99%
“…For example, Helou et al (2013) and Ergon et al (2015) conducted mid-IR studies of the Type IIb SN 2011dh in Messier 51 (see Filippenko 1997 for more information on supernova classification). The time evolution of its SED showed that the mid-IR emission became relatively brighter than optical emission at late times.…”
Section: Introductionmentioning
confidence: 99%